The Combustion Characteristics and Exhaust Gas Emissions of Stationary Diesel Engines Fueled with A Mixture of Diesel Fuel (Cinnamon Oil and Basil Oil) - Tiara Melinda; Roy Lamrun Sianturi; Rinaldo Hasudungan Malau (International Journal of Energy Systems and Materials Innovation, 2026)
The depletion of fossil fuels and strict emissions regulations have driven the need for renewable additives that can improve diesel combustion while reducing pollutants. This study experimentally examined the combustion characteristics and exhaust emissions of diesel fuel mixed with cinnamon oil and basil oil as dual additives in a single-cylinder stationary diesel engine. The essential oils were mixed into the diesel fuel at concentrations of 5%, 10%, and 15%, either individually or in combination, and tested at 1500 rpm with load variations of 0-100%. The results showed that the 10% dual additive mixture (DCB10) provided the best performance with a reduction in CO and HC emissions of 40.9% and 32.1%, respectively, compared to pure diesel fuel. However, NOx emissions increased by 8.5% due to high combustion temperatures and oxygen availability. The synergistic effects of the low viscosity of cinnamon oil and the antioxidant properties of basil oil improved atomization and oxidation kinetics, resulting in more complete combustion. Despite the increase in NOx, the environmental benefits remain positive, making the dual essential oil blend a promising bio-additive for cleaner diesel operation.